Fuzzy Controller from Experts’ Rules for Middle Axis Ball and Beam - Nguyen, Minh-Quan; Nguyen, Manh-Cuong; Trinh, Quang-Huy; Nguyen, Trung-Nghia; Ngo, Van-Thiet; Phu, Huynh-Manh-Trien; Nguyen, Pham-Minh-Duc; Nguyen, Phu-Tan; Le, Van-Truong; Dinh, Le-Hai-Duong; Dam, Thuan-An; Nguyen, Duc-Huy; Nguyen, Van-Dong-Hai (Journal of Fuzzy Systems and Control, 2023)
The present study examined the nonlinear system of Ball and Beam, to design an intelligent controller for this dynamic system. The authors formulated a mathematical model for the system and performed simulation testing using MATLAB to control it. It is noteworthy that the mathematical model was exclusively used for simulation purposes and not for building the controller. The author's team then proceeded to develop a Fuzzy Controller for the simulation model of the Ball and Beam system. Subsequently, the team tested the Fuzzy controller on the actual Ball and Beam model. The primary objective of this study was to assess the feasibility of building and controlling an intelligent controller for a nonlinear object, without relying on its mathematical model. The findings of the study can be useful in designing and controlling complex systems that are difficult to model mathematically.